Patient-reported outcomes, health-related quality of life, and acute medication use in patients with a ≥ 75% response to eptinezumab: subgroup pooled analysis of the PROMISE trials - Richard B. Lipton; Larry Charleston; Cristina Tassorelli; Thomas Brevig; Joe Hirman; Roger Cady (The Journal of Headache and Pain, 2022)
Abstract Background PROMISE-1 and PROMISE-2 evaluated the preventive efficacy, tolerability, and safety of eptinezumab, a calcitonin gene-related peptide–targeted monoclonal antibody, in adults with episodic (EM) and chronic migraine (CM), finding significant reductions in migraine frequency. This post hoc analysis compared patient-reported outcomes (PROs), health-related quality of life (HRQoL) and acute medication use in patients with a ≥ 75% migraine responder rate (MRR) after treatment with eptinezumab to patients with a ≥ 50– < 75% MRR. Methods PROMISE-1 and PROMISE-2 were phase 3, randomized, double-blind, placebo-controlled studies. This analysis included patients from both studies treated with eptinezumab 100 mg or 300 mg who experienced ≥ 75% and ≥ 50–< 75% MRR over Weeks 1–12 (wks1–12). In both studies, HRQoL was measured by the 36-item Short-Form Health Survey (SF-36) and acute medication usage. PROMISE-2 also included the 6-item Headache Impact Test (HIT-6), patient-identified most bothersome symptom (PI-MBS), and Patient Global Impression of Change (PGIC). Results In PROMISE-1, a total of 115/443 (26.0%; 100 mg, n = 49, 300 mg, n = 66) and 120/443 (27.0%; 100 mg, n = 61, 300 mg, n = 59) eptinezumab-treated patients achieved ≥ 75% and ≥ 50–< 75% MRR over wks1–12, respectively. In PROMISE-2, a total of 211/706 (30.0%; 100 mg, n = 95; 300 mg, n = 116) and 209/706 (29.6%; 100 mg, n = 110, 300 mg, n = 99) eptinezumab-treated patients achieved ≥ 75% and ≥ 50–< 75% MRR over wks1–12, respectively. EM and CM patients with ≥ 75% and ≥ 50–< 75% MRR over wks1–12 showed reduced use of acute headache medication and increased HRQoL to normative levels across SF-36 domains of bodily pain, social functioning, and physical functioning. In CM patients with ≥ 75% and ≥ 50–< 75% MRR over wks1–12, the mean change in HIT-6 total score with eptinezumab (pooled) was − 11.7 and − 7.6, respectively. “Very much” or “much” improvement responses were reported in 41.8% and 16.5% on PI-MBS and 36.2% and 20.0% on PGIC in ≥ 75% and ≥ 50–< 75% MRR, respectively. Conclusion Eptinezumab treatment induced a ≥ 75% MRR over wks1–12 in the majority of patients. This patient subgroup reported substantial improvements in PROs associated with headache-related life impact and HRQoL, and reductions in acute headache medication use, which were more marked than those in the ≥ 50–< 75% responders. This study supports the clinical meaningfulness of ≥ 75% MRR for patients with either EM or CM. Trial registration ClinicalTrials.gov identifiers: NCT02559895 (PROMISE-1), NCT02974153 (PROMISE-2).